2019
DOI: 10.1107/s160057751900033x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Rh2(CH3COO)4with thiols and thiolates: a structural study

Abstract: The structural differences between the aerobic reaction products of Rh 2 (AcO) 4 (1; AcO À = CH 3 COO À ) with thiols and thiolates in non-aqueous media are probed by X-ray absorption spectroscopy. For this study, ethanethiol, dihydrolipoic acid (DHLA; a dithiol) and their sodium thiolate salts were used. Coordination of simple thiols to the axial positions of Rh 2 (AcO) 4 with Rh-SH bonds of 2.5-2.6 Å keeps the Rh II -Rh II bond intact (2.41 AE 0.02 Å ) but leads to a colour change from emerald green to burgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The complex showed significant antitumor activity against Ehrlich-Lettre ascites carcinoma, [32][33][34] sarcoma 180 35 and lymphocytic leukemia L1210 36 and P388. 35 Further studies on the mechanism of action showed that the probable biomolecular targets of dinuclear rhodium(II,II) complexes are single-and double-stranded DNA, 35 proteins, [37][38][39][40][41][42][43][44][45][46] peptides 47,48 and amino acids, 31,[49][50][51] although the mode of binding to proteins has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The complex showed significant antitumor activity against Ehrlich-Lettre ascites carcinoma, [32][33][34] sarcoma 180 35 and lymphocytic leukemia L1210 36 and P388. 35 Further studies on the mechanism of action showed that the probable biomolecular targets of dinuclear rhodium(II,II) complexes are single-and double-stranded DNA, 35 proteins, [37][38][39][40][41][42][43][44][45][46] peptides 47,48 and amino acids, 31,[49][50][51] although the mode of binding to proteins has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The dirhodium tetraacetate complex [Rh 2 (μ-O 2 CCH 3 ) 4 ] includes a Rh­(II)–Rh­(II) bond with four carboxylates playing the role of bridging ligands arranged in a lantern-like form around the central bimetal unit, whereas neutral solvent molecules (L) occupy the axial coordination sites. Although causing toxic side effects, this complex has a proven activity against several cancer types, such as sarcoma 180, P388 leukemia, L1210 tumors, and Ehrlich-Lettre ascites carcinoma. Nevertheless, its mode of action is not yet disentangled despite several studies on its interaction with various proteins, although it is hypothesized that its biomolecular targets are single- and double-stranded DNA, proteins, peptides, , and amino acids. Moreover, interaction of dirhodium compounds with peptides and proteins was investigated in the framework of protein modification with the aim of designing artificial metalloenzymes. , Usually, Rh-based complexes are coordinated to proteins either via the covalent linkage, involving direct binding of these metal complexes to proteins, , or via the dative anchoring which is based on the formation of noncovalent interactions between protein atoms and Rh ligands as well as coordinative bonds between protein side chains and Rh centers . There are experimental pieces of evidence of the Rh-complex selectivity toward side chains of Asn, Asp, His, Lys, and the C-terminal carboxylate. ,, …”
Section: Introductionmentioning
confidence: 99%